The Profile of Teaching Skill Readiness of Candidate Teachers through Micro Teaching Practice in Unrika Batam - Sri Sugiharti (English Department, University of Riau Kepulauan, Batam,Indonesia, 2015)
The research objectives are to describe The Profile of Teaching Skill Readiness of Candidate Teachers through Micro Teaching Practice in UNRIKA Batam. In teaching skill readiness of candidate teachers here we can see from the result of strength and weaknesses of teaching learning activity in micro teaching practice. If the candidate teacher able to conduct an instructional procedure designed relate to the objective of teaching and material available.The result of this research can be used by all of parties, both internal and external stakeholder to improve teaching leaning readiness in micro teaching practice. The researcher gets the total of 154 data items which are categorized into two groups, namely strength (S) category which consists of 73 data items and weaknesses category which consist of 81 data items. Teaching are divided into two categorizations, they are ‘Strength’(S) and ‘Weaknesses’ (W). Key Words: Profile; Teaching; Readiness; and Candidate Teacher